Aplicabilidades dos protocolos de otimização neuro postural e otimização neuro psicofísica do conversor radioelétrico assimétrico – REAC - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Objective: To identify the scientific production about the applicabilities of REAC Technology Neuromodulation in the 2018-2023 time cut. Methods: This is an exploratory study, with studies captured in PubMed/MEDLINE, BDENF and LILACS databases using the keywords Asymmetric Electric Radio Transporter, REAC and Neuromudalation. Results: 11 articles were selected, being subdivided into five categories: "Correction of functional dysmetria with the Neuro Postural Optimization protocol (ONP-REAC)", "REAC neuromodulation protocols in children", "Neuro Psycho Physical Optimization in pathologies of the neurological and rheumatic system", "Therapeutic intervention in the triad depression, stress, anxiety with REAC technology" and "Effect of Neuromodulation REAC on chronic neuropathic pain". Conclusion: The information integrated in this review synthesized the scientific production about the applicabilities of REAC Technology Neuromodulation, which included a total of 11 studies, all with a quantitative approach, among them 1 open interventionist study, 1 retrospective study and 1 preliminary observational study. The protocols used were predominantly ONP followed by ONPF which are indicated for mood and behavior disorders. The anti-algic neuromodulation protocol (ANM) was also observed in use for post-herpetic chronic pain, suggesting the Neuromudalation REAC protocols as promising technology proven from favorable results in the attenuation of symptoms in various adverse clinical conditions.
Keywords: Neuromodulação; Otimização Neuro Postural (ONP); Otimização Neuro Psico Física (ONPF); Neuromodulação Antálgica (ANM); CNPQ::CIENCIAS DA SAUDE::ENFERMAGEM; ODS 3 – Saúde e bem-estar; ODS 4 – Educação de qualidade; ODS 9 – Indústria, inovação e infraestrutura